Light travel time effects in blazar flares - Finke, Justin D. (Frontiers in Astronomy and Space Sciences, 2024)
I present a model for light travel time effects for emission from a plasma blob in a blazar jet. This calculation could be incorporated into more complex models with particle acceleration and radiation mechanisms, but as presented here it is a agnostic as to these mechanisms. This model includes light travel time effects for an expanding or contracting blob. As an example, this model is applied to a flare observed by VERITAS and MAGIC from Mrk 421 in 2013; and to a flare observed by the Fermi Large Area Telescope from 3C 454.3 in 2010.